Towards Autonomous Robotic Systems 14th Annual Conference, TAROS 2013, Oxford, UK, August 28--30, 2013, Revised Selected Papers - Natraj, Ashutosh; Cameron, Stephen; Melhuish, Chris; Witkowski, Mark (Lecture Notes in Artificial Intelligence,, 2014)
This book constitutes the refereed proceedings of the 14th Conference on Advances in Autonomous Robotics, TAROS 2013, held in Oxford, UK, in August 2013. The 36 revised full papers presented together with 25 extended abstracts were carefully reviewed and selected from 89 submissions. The papers cover various topics such as artificial intelligence, bio-inspired and aerial robotics, computer vision, control, humanoid and robotic arm, swarm robotics, verification and ethics.